Preparation, Structure, Photoluminescent and Semiconductive Properties, and Theoretical Calculation of a Novel Cadmium Complex with Mixed Ligands - Xiu-Guang Yi; Wen-Tong Chen; Jian-Gen Huang; Ding-Wa Zhang; Yin-Feng Wang (Acta Chimica Slovenica, 2017)
A novel cadmium complex with mixed ligands {[Cd(2,2'-biim)(4,4'-bipy)(H2O)(ClO4)] (ClO4)}n (1) (2,2'-biim = 2,2'-biimidazole; 4,4'-bipy = 4,4'-bipyridine) has been synthesized through hydrothermal reaction and its crystal structure was determined by single-crystal X-ray diffraction technique. Single-crystal X-ray diffraction analyses revealed that complex 1 crystallizes in the space group Pna21 of the orthorhombic system and exhibits a one-dimensional zigzag chain structure consisting of [Cd(2,2'-biim)(4,4'-bipy)(H2O)(ClO4)]nn+ cationic chains and isolated ClO4– anions. Powder photoluminescent characterization reveals that complex 1 has an emission in the green region of the spectrum. Time-dependent density functional theory (TDDFT) calculation showed that the nature of the photoluminescence of complex 1 is originated from the ligand-to-ligand charge transfer (LLCT; from the HOMO of the perchlorate anions to the LUMO of the 4,4'-bipy ligand). A wide optical band gap of 3.25 eV was found by the solid-state UV/vis diffuse reflectance spectrum.